Efektivitas Pelayanan Jemput Bola Tim Gerak Kerja Cepat Dan Responsif (Jempol Tiger Japri) Dinas Kependudukan Dan Pencatatan Sipil Kota Semarang - Achmad Safna Al Azra; Ari Subowo; Augustin Rina Herawati (Journal of Public Policy and Management Review, 2023)
An Electronic Resident Identity Card or KTP-el is a population document that must be owned by every Indonesian citizen or Indonesian citizen aged 17 years or over. However, not all Indonesian citizens are required to have an e-KTP, especially the elderly. One of the reasons why elderly people do not have an e-KTP is limited ability or illness so they cannot record their e-KTP at the District Office or Disdukcapil. To overcome this, the Semarang City Disdukcapil provides an eKTP recording service for the elderly through the Jemput Bola Tim Gerak Kerja Cepat dan Responsif or JEMPOL TIGER JAPRI. This research aims to analyze the effectiveness of JEMPOL TIGER JAPRI services as a step to fulfill the ownership rights of e-KTP for the elderly in Semarang City. This research uses a qualitative descriptive method with data collection techniques through interviews, documentation and observation. The research was carried out at the Semarang City Population and Civil Registration Service and North Semarang District with informants who were involved in the JEMPOL TIGER JAPRI Service. Research informants were selected using purposive sampling technique. The theory used in this research is the theory of program effectiveness according to Sutrisno, which takes into account the phenomena of program understanding, target accuracy, timeliness, goal achievement and real change. The results of the research show that JAPRI JEMPOL TIGER services have not been running effectively because the results achieved and timeliness have not been optimal. Apart from that, the program monitoring factor which has not been implemented optimally is an obstacle to the effectiveness of JEMPOL TIGER JAPRI services